PERANCANGAN E-LEARNING DENGAN METODE COOPERATIVE LEARNING - Rio Andriyat Krisdiawan (NUANSA INFORMATIKA, 2013)
Cooperative Learning is a learning strategy that is interconnected and interconnected in tasks. E-Learning is learning and learning that uses electronic circuits (LAN, WAN, or Internet) to deliver lessons, interactions, or guidance. E-Learning design method used is Unifield Software Development Process (USDP) and phase work done in this research is inception and elaboration phase. The results of this study in the form of designing and planning the implementation of E-Learning System SMK Muhammadiyah 2 Brass with Cooperative Learning model.Keywords: Learning, Cooperative Learning, E-Learning, Unifield Software Development Process (USDP)